The Influence of Lunges and Rubber Load Exercises on Ap Chagi Kick Speed in UNTAD Taekwondo Club (UTC) Athletes - Marhadi Marhadi (International Journal of Research in Education, 2023)
The purpose of this study was to determine whether there was an effect of lunges training and rubber loads on Ap Chagi kick speed in UNTAD Taekwondo Club athletes who were the samples in this study. The method used in this research is an experimental method with a two-group pretest-posttest design. The research location is in the Mayor's Field. The population of this study was 20 athletes, so that the sampling was carried out using total sampling technique. Based on the calculation results, I found that: (1) There is an effect of Lunges training on Ap Chagi Kick Speed in UNTAD Taekwondo Club Athletes. With a t count value of 7,359 > t table of 2,262 (2) There is an effect of Rubber Load training on Ap Chagi Kick Speed in UNTAD Taekwondo Club Athletes with a t count value of 9,000 > t table of 2.262 (3) there is a difference in the effect of Lunges Exercise and Rubber Load on Ap Chagi Kick Speed in UNTAD Taekwondo Club Athletes. Evidenced by the increase between the pre-test and post-test Lunges is 3.520 with a mean deviation of 0.3300. While the Rubber Load obtained an increase between the pre-test and post-test was 3.800 with a mean deviation of 0.3000. Conclusion 1). There is an effect of Lunges training on Ap Chagi kick speed in UNTAD Taekwondo Club athletes with an increase of 3.4% 2). Rubber load on Ap Chagi kick speed on UNTAD Taekwondo Club athletes with an increase percentage of 3.5%. 3). There is a difference between lunges and rubber weights on the speed of Ap Chagi kicks in UNTAD Taekwondo Club athletes by 0.1%).